Structures of [M(Ura‐H)(H2O)n]+ (M = Mg, Ca, Sr, Ba; n = 1–3) complexes in the gas phase by IRMPD spectroscopy and theoretical studies. (9th March 2016) - Power, Barry; Haldys, Violette; Salpin, Jean‐Yves; Fridgen, Travis D.
Abstract : The structures of singly and doubly (and for Mg, triply) hydrated group 2 metal dications bound to deprotonated uracil were explored in the gas phase using infrared multiple photon dissociation spectroscopy in the mid‐infrared region (1000–1900 cm −1 ) and the O–H/N–H stretching region (2700–3800 cm −1 ) in a Fourier transform ion cyclotron resonance mass spectrometer. The infrared multiple photon dissociation spectra were then compared with the computed IR spectra for various isomers. Calculations were performed using B3LYP with the 6‐31 + G(d, p) basis set for all atoms except Ba 2+ and Sr 2+, for which the LANL2DZ or the def2‐TZVPP basis sets with relativistic core potentials were used. Atoms‐in‐molecules analysis was conducted for all lowest energy structures. The lowest energy isomers in all cases are those in which the one uracil is deprotonated at the N3 position, and the metal is coordinated to the N3 and O4 of uracil. Regardless of the degree of solvation, all water molecules are bound to the metal ion and participate in a hydrogen bond with a carbonyl of the uracil moiety. Copyright © 2016 John Wiley & Sons, Ltd.